2022
DOI: 10.1155/2022/6508046
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between the Gut and Brain in Ischemic Stroke: Mechanistic Insights and Therapeutic Options

Abstract: There has been a significant amount of interest in the past two decades in the study of the evolution of the gut microbiota, its internal and external impacts on the gut, and risk factors for cerebrovascular disorders such as cerebral ischemic stroke. The network of bidirectional communication between gut microorganisms and their host is known as the microbiota-gut-brain axis (MGBA). There is mounting evidence that maintaining gut microbiota homeostasis can frequently enhance the effectiveness of ischemic stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 176 publications
0
5
0
Order By: Relevance
“…5 , the research clusters out of date mainly referred to #0 Neurosciences, #1 Peripheral Vascular Disease, and #6 Multidisciplinary Sciences. Popular research clusters until 2022 were #2 Pharmacology & Pharmacy, #3 Medicine, General &Internal, #5 Biochemistry & Molecular Biology, and #7 Radiology, Nuclear Medicine & Medical Imaging, which are the hotspots in the exploration of ischemic stroke pathophysiology [ [61] , [62] , [63] , [64] , [65] ]. In general, the top 25 keywords, as well as their eight clusters, reflect a transition trend in ischemic stroke pathophysiology from the central system like cluster #0 Neurosciences to focusing on a holistic system like cluster #3 medicine, general & internal and mechanism-related keywords.…”
Section: Discussionmentioning
confidence: 99%
“…5 , the research clusters out of date mainly referred to #0 Neurosciences, #1 Peripheral Vascular Disease, and #6 Multidisciplinary Sciences. Popular research clusters until 2022 were #2 Pharmacology & Pharmacy, #3 Medicine, General &Internal, #5 Biochemistry & Molecular Biology, and #7 Radiology, Nuclear Medicine & Medical Imaging, which are the hotspots in the exploration of ischemic stroke pathophysiology [ [61] , [62] , [63] , [64] , [65] ]. In general, the top 25 keywords, as well as their eight clusters, reflect a transition trend in ischemic stroke pathophysiology from the central system like cluster #0 Neurosciences to focusing on a holistic system like cluster #3 medicine, general & internal and mechanism-related keywords.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study based on a mouse model of transient focal cerebral ischemia reported that intestinal T lymphocytes were trafficked into the meninges of the brain, wherein they induced neuroinflammation and the release of IL-17, which further facilitated the infiltration of immune cells into the damaged brain and promoted the secretion of proinflammatory cytokines [129]. Dysbiosis associates with post-stroke systemic inflammation, mediated partly by bacterial metabolites regulating microbiota-immune crosstalk [130]. The vagus nerve innervates the gutbrain axis, with vagal signaling maintaining intestinal barrier integrity and symbiosis [131].…”
Section: Brain-gut Axismentioning
confidence: 99%
“…There is a close connection between the gut microbiota and the CNS through neural, immune, endocrine, and metabolic pathways. Disturbances in the gut microbiota leads to neuroinflammation and promote microglia activation and pathological changes in brain tissue ( Huang et al, 2022 ). The gut microbiota may contribute to POCD through the gut-brain axis.…”
Section: Biological Mechanism Of Electroacupuncture For Postoperative...mentioning
confidence: 99%